Diagnostic Performance of Magnetic Resonance Enterography Disease Activity Indices Compared with a Histological Reference Standard for Adult Terminal Ileal Crohn's Disease: Experience from the METRIC Trial. (8th June 2022) - Kumar, Shankar; Parry, Thomas; Mallett, Sue; Bhatnagar, Gauraang; Plumb, Andrew; Walsh, Shaun; Scott, Nigel; Tandon, Ruchi; Chong, Heung; du Parcq, John; Martinez, Adrianna; Moorghen, Morgan; et al.
Abstract: Background and Aims: The simplified magnetic resonance enterography [MRE] index of activity [sMARIA], London, and 'extended' London, scoring systems are widely used in Crohn's disease [CD] to assess disease activity, although validation studies have usually been single-centre, retrospective, and/or used few readers. Here, we evaluated these MRE indices within a prospective, multicentre, multireader, diagnostic accuracy trial. Methods: A subset of participants [newly diagnosed or suspected of relapse] recruited to the METRIC trial with available terminal ileal [TI] biopsies was included. Using pre-specified thresholds, the sensitivity and specificity of sMARIA, London, and 'extended' London scores for active and severe [sMARIA] TI CD were calculated using different thresholds for the histological activity index [HAI]. Results: We studied 111 patients [median age 29 years, interquartile range 21-41, 75 newly diagnosed, 36 suspected relapse] from seven centres, of whom 22 had no active TI CD [HAI = 0], 39 mild [HAI = 1], 13 moderate [HAI = 2], and 37 severe CD activity [HAI = 3]. In total, 26 radiologists prospectively scored MRE datasets as per their usual clinical practice. Sensitivity and specificity for active disease [HAI >0] were 83% [95% confidence interval 74% to 90%] and 41% [23% to 61%] for sMARIA, 76% [67% to 84%] and 64% [43% to 80%] for the London score, and 81% [72% to 88%] and 41% [23% to 61%] for the 'extended' London score, respectively. The sMARIA had 84% [69-92%] sensitivity and 53% [41-64%] specificity for severe CD. Conclusions: When tested at their proposed cut-offs in a real-world setting, sMARIA, London, and 'extended' London indices achieve high sensitivity for active TI disease against a histological reference standard, but specificity is low.